Knowledge, Attitude, and Behavior of Tanjungpura University Undergraduate Students towards Nasopharyngeal Carcinoma - Imelda Dana Bella Ayu Fernanda; Sari Eka Pratiwi; Delima Fajar Liana (Universitas Muhammadiyah Yogyakarta, 2022)
Nasopharyngeal carcinoma is the most frequent head and neck cancer. The incidence of nasopharyngeal carcinoma significantly increased. Nasopharyngeal carcinoma is associated with risk factors linked to a lifestyle that usually begins in adolescence and young adulthood, such as undergraduate students. This research identifies undergraduate students' knowledge, attitude, and behavior about nasopharyngeal carcinoma. The study used a descriptive study with a cluster sampling method. As many as 100 undergraduate students from 8 faculties in Tanjungpura University filled out a questionnaire and analyzed using a statistical program with a descriptive statistical test. As much as 82% of respondents had received information about nasopharyngeal carcinoma from various sources. Knowledge was divided into 3 categories of levels, namely good (76-100% correct), fair (56-75% correct), and poor (56%). At the same time, attitude and behavior were divided into positive (score20) and negative (score20). The test results showed that the level of knowledge of the undergraduate students of 52% was good, the attitude was 100% positive, and the behavior was 100% positive. Therefore, undergraduate students at Tanjungpura University had good knowledge, a positive attitude, and positive behavior toward nasopharyngeal carcinoma. This study implies that adequate information is important in determining knowledge, attitudes, and behavior towards nasopharyngeal carcinoma.